Tourism Transformation In Canggu: Impacts On Socio-Cultural, Economic, And Environmental Dimensions With Sustainable Development Strategies - Ramadhan, Shofyan Hadi (Khasanah Ilmu - Jurnal Pariwisata Dan Budaya, 2024)
The village of Canggu in Bali has undergone a significant transformation from a traditional agricultural village to a commercial tourist destination. This article assesses the impact of tourism growth in Canggu since 2010, focusing on cultural change, economic aspects, and environmental impacts. Although local economic growth occurs through increased visits and development of tourist infrastructure, negative impacts also appear, including the disappearance of agricultural culture, changes in the lifestyle of local communities, and a decline in the quality of the environment. The study uses the paradigm of variable analysis to evaluate impacts in the socio-cultural, economic, and environmental dimensions. Data collection methods using literature studies. It was found that the positive economic impact could be offset by efforts to preserve culture, sustainable environmental management, and public involvement in tourism decision-making. This article also presents negative impact management plans, including involving communities in tourism decisions, protecting subterranean irrigation systems, and raising environmental awareness. In conclusion, sustainable tourism development in Canggu Village requires synergies between government, local communities, and tourists. By involving various stakeholders and implementing impact management measures, it is expected that Canggu Village can retain its cultural identity, support local economic growth, and maintain environmental balance during the rapid growth of the tourism sector.